IMPACTO DE HIPOMINERALIZACIÓN MOLAR-INCISIVO EN LA CALIDAD DE VIDA DE ESCOLARES DE UNA CLÍNICA ESTOMATOLÓGICA PERUANA - Tantalean-Santamaria, Annie Geraldine (2025)
Objective: To determine the impact of the Molar-incisor Hypomineralization (MIH) on quality of life in schoolchildren attending a University Stomatology Clinic, Pimentel, 2025. Materials and Methods: A quantitative, applied, non-experimental, cross-sectional and descriptive study. The sample was made up of 120 children aged 6 to 10 years. The sample consisted of 120 children aged 6 to 10 years. To assess the impact on quality of life, the Parent and Caregiver Perception Questionnaire (P-CPQ) was used, organized into four dimensions: oral symptoms, functional limitation, emotional well-being, and social well-being, consisting of 32 items. In turn, a data collection instrument was used to indicate gender, age, and degree of HMI, which was validated by expert judgment. Statistical tests such as ANOVA and chi-square were used, and were performed statistics program, SPSS version 25. Results: The impact of MIH is negative and significant on the dimensions of oral symptoms, functional limitation, and social well-being. Mild and moderate MIH was more prevalent in females (38.2% and 23.6%, respectively), and severe MIH in males (20%). In addition, the highest percentage of severe MIH was reported in children aged 6-7 years (31.4%). Schoolchildren with MIH reported greater impairment of quality of life. Conclusions: The presence of MIH negatively impacts oral health-related quality of life in the evaluated schoolchildren. Mild MIH was reported with the highest prevalence. Mild and moderate MIH were more prevalent in females, and severe MIH in males, the latter being more frequent in schoolchildren aged 6-7 years.